Lithium isotopic composition of benthic foraminifera: A new proxy for paleo-pH reconstruction. (1st September 2018) - Roberts, J.; Kaczmarek, K.; Langer, G.; Skinner, L.C.; Bijma, J.; Bradbury, H.; Turchyn, A.V.; Lamy, F.; Misra, S.
Abstract: The lithium isotopic composition of foraminifera is an established tracer of long-term changes in the global silicate weathering cycle, following the assumption that foraminifera faithfully record the lithium isotopic composition (δ 7 Li) of seawater. In this study, we demonstrate by utilising benthic foraminifera ( Amphistegina lessonii) that were cultured under decoupled pH-[CO3 2– ] conditions, that foraminifera δ 7 Li is strongly dependent on pH. This is reinforced with δ 7 Li data from globally distributed core-top samples of Cibicidoides mundulus and Cibicidoides wuellerstorfi, which show the same negative correlation with pH. The dependency of δ 7 Li on pH is perhaps a surprising result given that lithium speciation in seawater is independent of both pH and carbonate ion speciation. The dependence of lithium incorporation on growth rate was assessed by measuring the calcium isotopic composition; no growth rate dependent incorporation was observed. Instead, we propose that the strength of the 6 Li and 7 Li hydration spheres (and hence their respective desolvation energy) is pH-dependent, resulting in a significant isotopic fractionation during the incorporation of lithium into foraminifer calcite. The core-top derived δ 7 Li-pH calibration is used to demonstrate the applicability of this δ 11 B-independent pH proxy in reconstructing deglacial variations in pH in the South Pacific. The use of foraminifera δ 7 Li to compliment δ 11 B-based pH reconstructions has the potential to provide insight into time-dependent variations in porewater/seawater δ 11 B, temperature and salinity, which were previously unresolvable.